AN INVESTIGATION OF REFUGEE CHILDREN’S FEARS BASED ON CHILDREN’S AND PARENTS’ PERSPECTIVES - Szente, Judit; Taub, Gordon E.; Leppma, Monica (Southeast Asia Early Childhood Journal, 2014)
The study examined refugee children’s fears from a variety of perspectives. More specifically, the present study investigated 1) the effect of previous traumatic life events on refugee children’s present day fears, 2) the relationship between refugee children’s expressed fear objects and their projected fear objects, and 3) the relationship between refugee children’s expressed fear objects and parents’ knowledge of their child’s fear objects. Eighteen refugee child participants with a mean age of 9.64 years were included in the study along with their parent representatives. There were a total of 8 male and 10 female children with a mean residency length of 28 months in the United States. Results indicated a statistically significant relationship between prior traumatic events and refugee children’s present day expressed fear objects. Results did not suggest a statistically significant relationship between children’s self-expressed and projected fears. Similarly, there was no statistical significance between children’s expressed fears and their parents’ view of their children’s fears. Further discussion of results, conclusions, and implicationsre are included in the study.